Serologic Detection of Helicobacter pylori Infection and the Required Cautions - Maryam Esmaeili; Samaneh Saberi; Mehdi Alikhani; Mojgan Hatefi; Mohammad Tashakoripour; Mahmoud Eshagh Hosseini; Mohammad Ali Mohagheghi; Marjan Mohammadi (Pasteur Institute of Iran, 2016)
Introduction: Helicobacter pylori, as an etiologic cause of peptic ulcers and gastric cancer, should be tested and treated. The true state of infection can only be detected by isolation of gastric biopsies through the invasive method of gastroscopy. However, there are several non-invasive methods for detection of infection, the most common of which is serology. Methods: Here we have evaluated the efficacy of two commonly used commercial IgG-based ELISA kits (Kit-1 and Kit-2) against the endoscopy (biopsy)-based methods of rapid urease test (RUT) and bacterial culture. Our study population included 754 subjects categorized as having: 1) nonulcer dyspepsia (NUD, N=485), 2) peptic ulcer disease (PUD, N=65), and 3) gastric cancer (GC, N=204). Results: The rates of agreement between the results obtained by Kit-1, Kit-2 and both kits with culture/RUT were 62.4% (318 of 500, P=0.0001), 74.4% (183 of 246, P<0.0001), and 81.8% (117 of 143, P<0.0001), respectively. The agreement rate between the two kits, regardless of the results of the culture and RUT, was 83.6% (147 of 176, P<0.0001), leaving 16.4% of the subjects with discrepant results. The sensitivity rate and more drastically the specificity rates (against biopsy-based tests), claimed by Kit-1 (100% and 75%) and Kit-2 (>96% and >99%) were significantly reduced (Kit-1: 94.4% and 40.3%; Kit-2: 86.5% and 71%) for the Iranian population. Conclusion: Our data raises questions regarding the accuracy of commercial IgG-based ELISA kits for the detection of H. pylori infection. Therefore, caution should be practiced when such tests are used as the sole basis of medical decision making.